Methods for promoting knowledge exchange and networking among young professionals in the aerospace sector—IAF׳s IPMC workshop 2013 insights. (January 2016) - Monzon, Amalio; Chow, Tiffany; Guthrie, Paul; Lu, Zhuoyan; Chuma, Constant; He, Huang; Kuzkov, Sergii
Abstract: During the next decades, the aerospace community will pursue goals such as human exploration beyond the Moon, commercialization and cost reduction of space activities or sustainability of air transport and space operations, bringing relevant economic, environmental and social benefits to the society. Young professionals development is a critical success factor to enable these goals and in consequence is an area of significant interest. This paper focuses on the methods for promoting knowledge exchange and networking among Young Professionals. On the one hand, it analyzes the different activities currently used for that purpose by the organizations of the sector as well as explores the opportunities to reinforce these methods. On the other hand, it presents the results of a survey addressed to Young Professionals and aimed at identifying their needs, expectations and benefits perceived in relation with these activities. This study was conducted as part of the IAF׳s (International Astronautical Federation) IPMC (International Programme/Project Management Committee) Workshop held during the International Astronautical Congress (IAC) 2013 in Beijing, whose objective was to provide Young Professionals a forum to share experiences and to discuss ideas and needs, and which counted with more than fifty delegates representing IAF member organizations from all around the world. Highlights: A common trend on mixing trainings and hands on experience is observed. Structured development programs for knowledge transfer purposes are commonly used. Networking is attracting an increasing interest as workforce development tool. Existing methods have a positive impact in the motivation and engagement of young professionals. Organizations have room for improvement and best practices adoption.